Impact of Stress Hyperglycemia on No-Reflow Phenomenon in Patients with ST Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Mohamed Khalfallah; Dina A. Maria; Amany Allaithy (Ubiquity Press, 2022)
Background: Stress hyperglycemia is a common finding during acute myocardial infarction and associated with poor prognosis. To reduce the occurrence of no-reflow, prognostic factors must be identified before primary percutaneous coronary intervention (PPCI). Our objective was to investigate the impact of stress hyperglycemia in non-diabetic and diabetic patients on no-reflow phenomenon after PPCI. Methods: The study comprised 480 patients with ST elevation myocardial infarction (STEMI) who were managed by PPCI. Patients were classified into two groups according to thrombolysis in myocardial infarction (TIMI) flow grade: Group I (Patients with normal flow, TIMI 3 flow) and Group II (Patients with no-reflow, TIMI 0-2 flow). Patients were analyzed for clinical outcomes including mortality and major adverse cardiac events. Results: Incidence of stress hyperglycemia was 14.8% in non-diabetic patients and 22.2% in diabetic patients; the incidence of no-reflow phenomenon was 13.5% and no-reflow was significantly higher in patients with stress hyperglycemia. Multivariate regression analysis identified the independent predictors of no-reflow phenomenon: stress hyperglycemia OR 3.247 (CI95% 1.656-6.368, P = 0.001), Killip class >1 OR 1.893 (CI95% 1.004-3.570, P = 0.049) and cardiogenic shock OR 3.778 (CI95% 1.458-9.790, P = 0.006). Conclusion: Stress hyperglycemia was associated with higher incidence of no-reflow phenomenon. The independent predictors of no-reflow were stress hyperglycemia, Killip class >1 and cardiogenic shock.